2
$\begingroup$

I am still fiddling with the understanding and application of the fractional integration/differentation.
I've tried the wikipedia-formula for the Cauchy's iterated integration: $$ (J^{\alpha} f)(x) = \frac 1{\Gamma(\alpha)} \cdot \int_0^x((x-t)^{\alpha-1}f(t)) dt$$ and inserted $$ (J^{1/2} f)(x) = \frac 1{\Gamma(1/2)} \cdot \int_0^x (x-t)^{-1/2} f(t) dt$$ applied to the function $f(x) = \exp(x)-1$ .

Two time the semi-integral for some interval $0 \ldots x$ should reproduce the usual integral, but I get a difference for any $x$ that I try.

Q: Where is the error in the understanding/implementation of the half-integral?


This is, what I've done in Pari/GP:

semiInt(x,d=1e-64)= 1/gamma(1/2) * intnum(t=0,x-d,(x-t)^(1/2-1)*(exp(t)-1))
        \\ introduce a delta-deviation "d" for the upper bound to prevent 
        \\  evaluation  with 0^(-1/2) when the formal parameter t=x

x1=0.5                          \\  = 0.500000000000      
x2 = semiInt(semiInt(x1))       \\  = 0.161464182768
x3 = intnum(t=0,x1,exp(t)-1)    \\  = 0.148721270700
x2-x3                           \\  = 0.0127429120679
$\endgroup$
2
  • $\begingroup$ You want to compute a function $f_2$, say, as the semi-integral of $f$, then compute the semi-integral of $f_2$. You have only $f(t) = \exp(t)-1$ in your formula. $\endgroup$ – GEdgar Oct 9 '13 at 14:30
  • $\begingroup$ @GEdgar: I just assumed that "semi-integral" gives a function, which composed with itself gives the ordinary integral: $b=semiInt(0,a);c=semiInt(0,b); c=?=Int(0,a) $. Did I misunderstand something here? $\endgroup$ – Gottfried Helms Oct 9 '13 at 14:36
3
$\begingroup$

Symbolically... Let $f(x) = e^x-1$. Then I get $$ J^1f(x) = e^x-x-1, \\ f_2(x):= J^{1/2}f(x) = \frac{e^x \sqrt{\pi}\;\text{erf}\sqrt{x} - 2\sqrt{x}}{\sqrt{\pi}}\\ J^{1/2}f_2(x) = \frac{1}{\pi}\int_0^x\frac{e^t \sqrt{\pi}\;\text{erf}\sqrt{t} - 2\sqrt{t}}{\sqrt{x-t}}\;dt . $$ If we did not know where this integral came from, perhaps we would be amazed by the assertion $$ \frac{1}{\pi}\int_0^x\frac{e^t \sqrt{\pi}\;\text{erf}\sqrt{t} - 2\sqrt{t}}{\sqrt{x-t}}\;dt = e^x-x-1 $$ But this is simply $J^1 f = J^{1/2} J^{1/2} f$, which is how the fractional integral is supposed to act.

$\endgroup$
4
  • $\begingroup$ Hmm, I could reproduce the ordinary integral $(J^1f)(x)$ with this. Do I understand it correctly: the Cauchy's semi-integral-formalism should be applied to some (beforehand) unknown function $f_2(x)$ such that $(J^{1/2}f_2)(x) = (J^1 f)(x) $. Then find an appropriate function $f_2(x)$ ? - Well, I've difficulties to understand this because I'm much conditioned for functional composition which seems a completely different rationale... $\endgroup$ – Gottfried Helms Oct 9 '13 at 15:36
  • $\begingroup$ And more generally, $J^a J^b f = J^{a+b} f$. $\endgroup$ – GEdgar Oct 9 '13 at 16:27
  • $\begingroup$ Please see my comment in a new "own answer"-box. Thanks for your explanations! $\endgroup$ – Gottfried Helms Oct 9 '13 at 16:47
  • $\begingroup$ Perhaps in the 3rd formula it could be made more explicite, that inside the integral is the previously defined function $f_2(x)$ such that $J^{1/2}f_2(x) = \frac 1{\sqrt {\pi}} \int_0^x f_2(t) (x-t)^{-1/2} dt $ which occurs visibly after expanding/cancelling of $\sqrt {\pi}$ $\endgroup$ – Gottfried Helms Oct 9 '13 at 17:25
0
$\begingroup$

This is a comment for G.Edgar's answer, but too long for a comment-box.

Ahh, I see now: what I did was iterating the half-integral over its result, in the sense of $$ \int_0^{\int_0^x f(u) du} f(t) dt $$ instead of $$ \int_0^x \left( \int_0^t f(u) du \right) dt $$

(Of course, I should write here the semi-integral-notation, but I only want to point out the conceptional aspect)

Thanks, Gerald! I think I can now proceed on my own... I'll have some more questions another day, though.


So I should write:
$$ \begin{array}{lllllr} f(x) &=& \exp(x)-1 & &&&(1)\\ f_1(x,x_0=0) &=& (J^{1/2} f){\Large |}_{x_0}^x &=& \frac 1{\sqrt{\pi}} \int_{x_0}^x (x-t)^{-1/2} f(t) dt &&(2)\\ f_2(x,x_0=0) &=& (J^{1/2} f_1){\Large |}_{x_0}^x &=& {1 \over \sqrt{\pi}} \int_{x_0}^x (x-t)^{-1/2} f_1(t,x_0) dt &&(3) \end{array} $$ to arrive, of course, at equality:

$ \displaystyle \begin{array}{lllllrrr} \phantom{aaaaa}&f_2(x,x_0=0) &=& (J^1 f){\Large |}_{x_0}^x &=& \int_{x_0}^x f(t) dt &\phantom{aaaaaaaaaa}&\phantom{aaaaa}&(4) \end{array}$

Moreover, (according to G.Edgar's answer) we have some shortcuts (or "more closed forms") for the integrals:
$$\begin{array} {llll}(J^1 f)(x) &=& \int f(t) dt &=& (e^x-1) - x &&&(5) \\ (J^{1/2} f)(x) &=& && e^x\text{erf}(\sqrt{x}) - 2{\sqrt{x}\over\sqrt{\pi}} &&&(6) \\ \text{ semi-derivative} \\ (J^{-1/2} f)(x) &=& \frac d{dx}(J^{1/2}f)(x) &=& e^x\text{erf}(\sqrt{x}) &&&(7, \text{ WA }) \\ \end{array}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.